66.0k views
3 votes
What is the solution to the equation –5w + 3 = 4w – 6?

User Pufferfish
by
5.2k points

2 Answers

4 votes

Answer:

-2=2

Explanation:

User David Moles
by
6.0k points
3 votes

Answer:

w = 3

Explanation:

-5w + 3 = 4w - 6

were going to get the variable and the numbers on different sides

-5w + 3 - 3 = -5w

4w - 6 - 4w = -6

-5w + 4w = -1w or -w

-6 + 3 = -3

-w = -3

and since there're both negatives you can just take that away and you get

w = 3

User Dimba
by
4.9k points